THE DEVELOPMENT OF INNOVATIVE MEDIA TO STRENGTHEN PARTICIPATION IN THE DEVELOPMENT OF RAJAMANGALA UNIVERSITY OF TECHNOLOGY SUVARNABHUMI TO BE A GREEN UNIVERSITY - Kesanuch, Sompong; Rangmeesrisuk, Jidapa; Chaiyanich, Parinut; Kracheachan, Chanidapa; Klinchandaeng, Tanamon (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to 1) study the factors influencing engagement and innovative media formats that affect Participation in developing the Rajamangala University of Technology Suvarnabhumi to be a green university, 2) develop innovative media, experiment and evaluate innovative media to enhance Participation in the development of Rajamangala University of Technology Suvarnabhumi to become a green university. This research used mixed methods research comprising both qualitative research and quantitative research methods. The sample consisted of 859 personnel and students, seven experts in media development and engagement, and experimented with innovative media by 400 students. The research tool was a questionnaire. Innovative media suitability assessment form And satisfaction assessment form Data were analyzed using descriptive statistics consisting of Frequency, Percentage, Mean, Standard Deviation, and Inferential Statistics Analysis, consisting of Coefficients, Pearson Correlation, and Multiple Linear Regression Analysis. The results of the research were as follows: 1) 1.1) The factors affecting Participation in university development towards a green university were factors of environmental conservation activities, factors of environmental policy of the university, factors of government environmental policy, and factors of social, environmental conservation values with statistical significance at the .01 level, 1.2) Type of media, media objectives and media access channels affected their Participation in university developed into a green university; 2) The development of innovative media resulted in two types of innovative media: 2.1) video media and 2.2) poster media. And 3) the results of the innovative media experiment showed a high level of satisfaction ( = 4.209), and The overall evaluation of the suitability of the innovative media was at the highest level ( = 4.520). The results of the study as mentioned above have provided innovative media models for enhancing Participation. Raising awareness of environmental conservation will lead to cooperation in developing the university to become a green university.